Heart rate increase after pulmonary vein isolation predicts freedom from atrial fibrillation at 1 year. (10th November 2019) - Goff, Zackary D.; Laczay, Balint; Yenokyan, Gayane; Sivasambu, Bhradeev; Sinha, Sunil K.; Marine, Joseph E.; Ashikaga, Hiroshi; Berger, Ron D.; Akhtar, Tauseef; Spragg, David D.; Calkins, Hugh
Abstract: Introduction: Ablation of atrial vagal ganglia has been associated with improved pulmonary vein isolation (PVI) outcomes. Disruption of vagal reflexes results in heart rate (HR) increase. We investigated the association between HR change after PVI and freedom from atrial fibrillation (AF) at 1 year. Methods and Results: Patients who underwent PVI for paroxysmal AF were identified from the Johns Hopkins Hospital AF registry. Electrocardiograms taken pre‐PVI and post‐PVI were used to determine the change in HR. Patients followed‐up at 3, 6, and 12 months. Of 257 patients (66% male, age 59+/‐11 years), 134 (52%) remained free from AF at 1 year. The average HR increased from 60.6 ± 11.3 beats per minute (bpm) pre‐PVI to 70.7 ± 12.0 bpm post‐PVI. Patients with recurrence of AF had lower post‐PVI HR than those who remained free from AF (67.8 ± 0.2 vs 73.3 ± 13.0 bpm; P  <.001). The probability of AF recurrence at 1‐year decreased as the change in HR increased (estimated odds ratio [OR], 0.83; 95% confidence interval [CI, 0.74‐0.93]; P  = .002). HR increase more than 15 bpm was associated with the lowest odds of AF recurrence (estimated OR, 0.39; 95% [0.17‐0.85]; P  = .018) compared to HR decrease. Conclusions: Resting HR was found to increase after PVI. Increase in HR more than 15 bpm has a positive association with remaining free from atrial fibrillation at 1 year.